2018
DOI: 10.1158/1541-7786.mcr-17-0215
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Uracil DNA Glycosylase Selectively Resensitizes p53-Mutant and -Deficient Cells to 5-FdU

Abstract: Thymidylate synthase (TS) inhibitors including fluoropyrimidines [e.g., 5-Fluorouracil (5-FU) and 5-Fluorodeoxyuridine (5-FdU, floxuridine)] and antifolates (e.g., pemetrexed) are widely used against solid tumors. Previously, we reported that shRNA-mediated knockdown (KD) of uracil DNA glycosylase (UDG) sensitized cancer cells to 5-FdU. Because p53 has also been shown as a critical determinant of the sensitivity to TS inhibitors, we further interrogated 5-FdU cytotoxicity after UDG depletion with regard to p53… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 48 publications
(91 reference statements)
1
31
0
Order By: Relevance
“…Moreover, HDACi-mediated inhibition of certain DNA repair pathways can be exploited to increase efficacy and/or to overcome drug resistance. Increased cytotoxicity of 5-fluorouracil has been reported when combined with HDACi [66,67] and one study has demonstrated that loss of UNG resensitizes cells to 5-fluorodeoxyuridine (5-FdU) [68]. Our findings provide a mechanistic explanation for these observations and warrant further investigation on combinatorial effects of HDACi-and antifolate regimens.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, HDACi-mediated inhibition of certain DNA repair pathways can be exploited to increase efficacy and/or to overcome drug resistance. Increased cytotoxicity of 5-fluorouracil has been reported when combined with HDACi [66,67] and one study has demonstrated that loss of UNG resensitizes cells to 5-fluorodeoxyuridine (5-FdU) [68]. Our findings provide a mechanistic explanation for these observations and warrant further investigation on combinatorial effects of HDACi-and antifolate regimens.…”
Section: Discussionsupporting
confidence: 52%
“…Since UDG depletion is known to sensitize cancer cells to chemotherapy, 93 the ability of the identied UDG inhibitor A8 to synergize with the anticancer drug, 5-FU, was next investigated in prostate cancer cells. Using the Chou-Talalay method, signicant synergism was shown between A8 and 5-FU at inhibiting RM-1 cell proliferation (Fig.…”
Section: Combination Studies Of Udg Inhibitors and 5-fu Against Prostmentioning
confidence: 99%
“…Instead, 5-FU cytotoxicity under the conditions employed was found to be mainly due to its incorporation into RNA rather than the DNAmediated effects [16]. However, Yan et al [18] pointed out that p53 status together with UNG plays a role in determining the cytotoxicity of 5-Fluoro-2'-deoxyuridine (5-FdU, floxuridine), another fluoropyrimidine that is efficiently incorporated into DNA rather than RNA. In absence of UNG, genomic 5-FU was found to block replication and induce double-strand breaks [125].…”
Section: Sensitizing Cells To Cancer Therapy-induced Dna Damagementioning
confidence: 99%
“…Moreover, many (if not most) classical chemotherapeutic treatments exert their anti-cancer effect through damage to DNA [8,9]. Irradiation [10][11][12][13][14][15], fluoropyrimidines [16][17][18], antifolates [19][20][21], platinum drugs [22][23][24][25][26][27][28], demethylating agents [29], anthracyclines and monofunctional alkylating agents such as temozolomide [30][31][32] have been shown to directly or indirectly cause the DNA damage that is typically repaired by BER. Despite progress in immuno-and targeted therapies, these classical cancer treatment agents are likely to also be extensively used in the future.…”
Section: Introductionmentioning
confidence: 99%